The Phenomenon of Money Politics and Nigeria’s Democratization: An Exploration of the Fourth Republic - Tunde, Sakariyau Rauf; Lawal, Aliu Fatima; Muhammed, Adamu (Journal of Social Economics Research, 2015)
It is an established fact that money politics is a global phenomenon, its trend in Nigeria’s electoral system is worrisome. Buying and selling of votes has become an accepted norm in Nigeria’s political arrangement and which threatens her readiness to embrace democratic virtues. Vying for political posts is left for rich individuals due to the huge amount of money involved in preparation for elective offices. Though the electoral act regulates political finance, its application is not obtainable. The electoral body that is responsible for monitoring and regulating expenses of candidates has not been vibrant in such obligation. This makes it imperative in this study to explore the ugly phenomenon of money politics in Nigeria’s democracy via its implication for sustainable development. The paper infers that until Nigerians move from politics of money and adopt politics of ideology and creativity, advancement of the country’s democracy might be a mirage.